Implementasi Langkah Penyusunan Rencana Strategi Pendidikan Studi Kasus SMP Negeri 1 Pematangsiantar - Enjel Oktaviany Simanjuntak; Aulia Christina Sinaga; Rosvina Sari Siburian; Eka Daryanto (Program Studi Pendidikan Biologi, 2023)
The management function is the function of managing organizational components to achieve goals effectively and efficiently. Plans must be made to achieve the goals set. The existence of a plan encourages the implementation of organizational activities to achieve goals. Planning is the starting point of all activities, while the strategy is how we do something to achieve the goals that have been set. A strategic plan is a plan that is carried out to achieve the goals of the organization, the hope of which is from choosing a strategy to realizing the goal of obtaining a lot of problem solving so that the error rate that may occur is smaller. In this study, the authors used a descriptive method. The population in this study were educators and support staff at SMP Negeri 1 Pematangsiantar and used saturated sampling where the entire population was sampled. One of the techniques in making strategic planning is to carry out a SWOC analysis. The results of the analysis of internal and external factors greatly influence the life processes of organizations and educational institutions. Internal factors are factors within the organization/institution. Good communication by managers and employees creates a pleasant work environment.